INCREASING STUDENTS’ VOCABULARY MASTERY BY USING WORD WALL METHOD OF THE SECOND GRADE AT SMP NEGERI 4 TOLITOLI UTARA - Moh Firmansyah (Jurnal Madako Education, 2018)
The objective of this research is to identify the used word wall method in increase students’ vocabulary. An experimental design is used to collect the data. The researcher take the second grade of SMP Negeri 4 Tolitoli Utara as object of the research.The data are obtain through a pre-test and post-test. The pre-test is used to measure the students previous ability in memorizing vocabulary, the treatment are apply materials through word wall method, and the post-test is use to find out the students’ vocabulary after give the treatment.The result of the analysis show the effectiviness of word wall in increasing vocabulary. It can be see by the difference of the mean score between pre-test and post-test. The mean score of pre-test is 18.67 while in the post-test improve up to 47.89. Moreover the Minimum Mastery Criterion of English lesson is 75 (seventy-five). Then the data of both test are analyze by using T-test, and the result show that the T-test value 14.030 is greater than T-table value 2,048. It can be infer that word wall method is very effective in increasing students’ vocabulary in memorizing vocabulary. Key words: word wall, vocabulary, memorize vocabulary.